2017
DOI: 10.1016/j.jvs.2016.07.115
|View full text |Cite
|
Sign up to set email alerts
|

Stenting versus endarterectomy after prior ipsilateral carotid endarterectomy

Abstract: In this population-based study, we have shown higher mortality but similar stroke and MI associated with redo CEA compared with CAS after prior ipsilateral CEA. We recommend avoidance of redo CEA in very sick patients. Smoking cessation remains a potent target for improvement of outcomes of carotid revascularization in these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
24
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 36 publications
3
24
0
Order By: Relevance
“…4,12 A possible explanation for this finding is that the present study used a very accurate otolaryngological surveillance program, while in the majority of the published studies, the diagnosis of cranial nerve injuries was surgeon driven; this could have contributed to the diagnosis of minimal peripheral lesions in the current study, which might be under reported in other series. 5 Furthermore, in the present study the majority of cranial nerve injuries were reversible, and when the rate of permanent lesions only was analysed, the percentage of cranial nerve injuries fell to 3%, which is in line with the data in the literature.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…4,12 A possible explanation for this finding is that the present study used a very accurate otolaryngological surveillance program, while in the majority of the published studies, the diagnosis of cranial nerve injuries was surgeon driven; this could have contributed to the diagnosis of minimal peripheral lesions in the current study, which might be under reported in other series. 5 Furthermore, in the present study the majority of cranial nerve injuries were reversible, and when the rate of permanent lesions only was analysed, the percentage of cranial nerve injuries fell to 3%, which is in line with the data in the literature.…”
Section: Discussionsupporting
confidence: 92%
“…Most importantly, the duration of follow-up was similar between the two groups, while previous studies have observed a significantly shorter follow-up time in CAS patients. 5 Followup results were fairly good, with satisfactory survival rates and a very limited number of neurological events at 5 years. In their meta-analysis, Fokkema et al 3 reported only seven strokes and seven deaths during follow-up among 453 patients treated by CAS and 731 patients treated by redo CEA, after a mean follow-up of 13 months.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…Numerous studies investigated association between carotid plaques progression and the risk of cerebrovascular events in patients with asymptomatic carotid stenosis [29,30]. Most of the previous studies used standard flow velocity [31].…”
Section: Discussionmentioning
confidence: 99%